Nitrogen in the Home Landscape - Amy L. Shober (EDIS)
SL-254, 3-page illustrated fact sheet by Amy L. Shober, helps homeowners understand how N interacts in the environment through the nitrogen cycle, making maintenance of home landscapes or gardens easier and more sustainable. Published by the UF Soil and Water Sciences Department, December 2007.